The financial system and the economy : principles of money & banking - Burton, Maureen; Lombra, Raymond E. (Mason, Ohio : Thomson/South-Western, 2006)
The book captures the ongoing changes in the financial system, particularly with regard to technology and globalization. Secondly, to present an analytical framework that enables students to understand and anticipate changes in the financial system and the accompanying changes in the financial markets and institutions.
Includes bibliographical references and index.
uaj 30/04/13
Loans
Keywords: Finance; Money; Banks and banking; Financial institutions; Financial services industry